2018
DOI: 10.1002/jgh3.12043
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal tuberculosis: Uncommon of common

Abstract: Background and AimEsophageal involvement in tuberculosis (TB) is rare and is usually secondary. Data on esophageal TB are scarce. We aimed to analyze clinical and endoscopic features and outcomes of treatment in esophageal TB.MethodsWe retrospectively identified patients with esophageal TB from January 2014 to December 2016 at GB Pant Hospital. Well‐defined granuloma with or without caseation and/or acid‐fast bacilli on staining either from esophageal biopsy or the adjacent mediastinal lymph node fine‐needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
(39 reference statements)
0
22
0
2
Order By: Relevance
“…[ 34 36 40 ] It is predominantly secondary to spread from contagious intrathoracic viscera, though primary OTB with isolated esophageal lesions has been described. [ 48 57 58 59 ] The lesions are seen predominantly to involve the middle third of the esophagus in the form of ulcers[ 60 61 ]; rarely, the lesions may be proliferative appearing as malignancy or submucosal growth. [ 48 59 ] Complications in the form of abscesses, stricture, perforation, bleeding and fistulas to adjacent structures like trachea, bronchi, mediastinum and aorta may be the presenting features of OTB.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[ 34 36 40 ] It is predominantly secondary to spread from contagious intrathoracic viscera, though primary OTB with isolated esophageal lesions has been described. [ 48 57 58 59 ] The lesions are seen predominantly to involve the middle third of the esophagus in the form of ulcers[ 60 61 ]; rarely, the lesions may be proliferative appearing as malignancy or submucosal growth. [ 48 59 ] Complications in the form of abscesses, stricture, perforation, bleeding and fistulas to adjacent structures like trachea, bronchi, mediastinum and aorta may be the presenting features of OTB.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In summary, there are three types of mode of involvement of ET according to the method of infection [ 3 , 5 ]: Type 1, secondary ET, is the most common type and is often secondary to tuberculosis in adjacent organs and tissues, such as paraesophageal or mediastinal lymph node tuberculosis; paraesophageal lesions of the esophagus have often been missed in the pre-EUS era. Puri R et al [ 16 ] showed that ET was commonly secondary to mediastinal lymph nodal involvement in 32 cases of ET, and EUS showed lymph nodes adjacent to esophageal pathology in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal tuberculosis (ET) is relatively rare, accounting for < 0.2% of all tuberculosis (TB) patients [ 1 3 ]. The clinical manifestations are often not specific, including mucosal or submucosal eminence lesions, ulcer, fistula [ 4 ], and others [ 5 ]. A definite diagnosis of ET requires finding acid-fast bacilli or caseous necrotizing granuloma [ 6 ], which is challenging in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Поражение пищевода при туберкулезе наиболее часто наблюдается в грудном отделе и характеризуется наличием вытянутых изъязвлений или специфической инфильтрации стенки [69][70][71][72]. При туберкулезе пищевода эндоскопическая биопсия не всегда информативна в связи с частым распространением патологического процесса из средостения и поражением наружных слоев стенки пищевода.…”
Section: уровень убедительности рекомендаций a (уро вень достоверностunclassified